Autonomous wearable sweat rate monitoring based on digitized microbubble detection. Issue 22 (21st October 2022) - Lin, Haisong; Yu, Wenzhuo; Suarez, Jorge Emiliano De Dios; Athavan, Harish; Wang, Yibo; Yeung, Christopher; Lin, Shuyu; Sankararaman, Sriram; Milla, Carlos; Emaminejad, Sam
Abstract : A digitized microbubble detection mechanism delivered by a hybrid microfluidic/electronic system is devised for autonomous wearable high signal-to-noise ratio sweat rate monitoring. Abstract : Advancements in wearable bioanalytical microsystems have enabled diurnal and (semi)continuous monitoring of physiologically-relevant indices that are accessible through probing sweat. To deliver an undistorted and physiologically-meaningful interpretation of these readings, tracking the sweat secretion rate is essential, because it allows for calibrating the biomarker readings against variations in sweat secretion and inferring the body's hydration/electrolyte homeostasis status. To realize an autonomous wearable solution with intrinsically high signal-to-noise ratio sweat rate sensing capabilities, here, we devise a digitized microbubble detection mechanism—delivered by a hybrid microfluidic/electronic system with a compact footprint. This mechanism is based on the intermittent generation of microliter-scale bubbles via electrolysis and the instantaneous measurement of their time-of-flight (and thus, velocity) via impedimetric sensing. In this way, we overcome the limitations of previously proposed sweat rate sensing modalities that are inherently susceptible to non-targeted secretion characteristics (pH, conductivity, and temperature), constrained by volume, or lack system integration for autonomous on-body operation. By deploying our solution in human subject trials, we validate the utility of our solution for seamless monitoring of exercise- and iontophoretically-induced sweat secretion profiles.